(untitled) (International Seven Journal of Multidisciplinary, 2025)
The capture and use of rainwater are essential strategies for the conservation of water resources and the strengthening of global water security. With the increase in demand for drinking water and the degradation of water sources, sustainable catchment systems have become fundamental for integrated water management. In Brazil, the unequal distribution of water and extreme weather events reinforce the need for these practices. Among the main techniques, green infrastructure, reforestation, soil management and individual and urban catchment systems stand out, which enable the use of water for non-potable purposes, relieving pressure on water sources. Studies show that these initiatives contribute to the recharge of aquifers, reduction of surface runoff and flood mitigation, in addition to promoting savings in the consumption of drinking water in urban and rural areas. Success stories, such as the systems implemented in the Federal District and São Paulo, show the benefits of these solutions in reducing the consumption of treated water and in environmental preservation. In addition, private initiatives and public policies have proven effective in encouraging sustainable practices, such as payment for environmental services. The implementation of infiltration wells and other sustainable urban drainage techniques reinforces the importance of rainwater harvesting as a solution to contemporary water challenges, ensuring greater resilience of supply systems and promoting sustainable development.